High Power (>27 W) Semiconductor Disk Laser Based on Pre-Metalized Diamond Heat-Spreader - Guan-Yu Hou; Shi-Li Shu; Jian Feng; Andreas Popp; Berthold Schmidt; Huan-Yu Lu; Li-Jie Wang; Si-Cong Tian; Cun-Zhu Tong; Li-Jun Wang (IEEE Photonics Journal, 2019)
High power semiconductor disk lasers (SDLs) were demonstrated based on the thermal management using pre-metalized diamond heat-spreader. The processing of pre-metallization using Cu-Sn alloy was developed. The resultant and influence of pre-metallization on the thermal performance of SDLs were investigated. It was found that the pre-metalized diamond heat-spreader was able to improve effectively not only the thermal resistance but also the bonding quality. 38% decrease on the thermal resistance of SDL was realized. The CW power exceeding 27 W, limited by the available pump power, was demonstrated.